2010
DOI: 10.1007/s10799-010-0066-1
|View full text |Cite
|
Sign up to set email alerts
|

Information security in networked supply chains: impact of network vulnerability and supply chain integration on incentives to invest

Abstract: Recent supply chain reengineering efforts have focused on integrating firms' production, inventory and replenishment activities with the help of communication networks. While communication networks and supply chain integration facilitate optimization of traditional supply chain functions, they also exacerbate the information security risk: communication networks propagate security breaches from one firm to another, and supply chain integration causes breach on one firm to affect other firms in the supply chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 31 publications
2
30
2
Order By: Relevance
“…Recent research has suggested several dimensions that have a substantial influence on a SC's vulnerability to cyber risk. These include different network configurations (Bandyopadhyay et al, 2010;Zhang et al, 2012), firm sizes (Tran et al, 2016), corporate cultures (Xue et al, 2013), industry sectors (Sharma and Routroy, 2016;Tran et al, 2016) and business principles (Durowoju et al, 2012;Charitoudi and Blyth, 2014). This research found that most studies take a generic perspective, and therefore, this study pinpoints the need for contextualised studies that address such dimensions in-depth to relate specific cyber risks to specific dimensions.…”
Section: A Research Agenda For Managing Cyber Risk In Supply Chainsmentioning
confidence: 76%
See 1 more Smart Citation
“…Recent research has suggested several dimensions that have a substantial influence on a SC's vulnerability to cyber risk. These include different network configurations (Bandyopadhyay et al, 2010;Zhang et al, 2012), firm sizes (Tran et al, 2016), corporate cultures (Xue et al, 2013), industry sectors (Sharma and Routroy, 2016;Tran et al, 2016) and business principles (Durowoju et al, 2012;Charitoudi and Blyth, 2014). This research found that most studies take a generic perspective, and therefore, this study pinpoints the need for contextualised studies that address such dimensions in-depth to relate specific cyber risks to specific dimensions.…”
Section: A Research Agenda For Managing Cyber Risk In Supply Chainsmentioning
confidence: 76%
“…Smith et al (2007) recommend that SC integration, by aligning systems and processes, will yield better returns through standardised ways of working, shared security objectives and better general communication (see conceptual model, Figure 10). Bandyopadhyay et al (2010) argue that higher levels of integration and collaboration reduce free-riding behaviour when considering investment in cyber security.…”
Section: Inter-organizational Collaborationmentioning
confidence: 99%
“…For example, the well know Electronic Data Interchange (EDI) and the more recent Continuous Replenishment Program that link manufacturers, distributors, and retailers within a supply chain [15].…”
Section: A the Problemmentioning
confidence: 99%
“…Nevertheless, better interconnection does not come without risks. Modern IT has eliminated security barriers around resources and systems thus, given supply chains more opportunities to achieve better profitability and customer satisfaction by reducing production and inventory wastes (Svensson 2002) while on the contrary, put them into a higher possibility of disruption (Smith et al 2007;Bandyopadhyay et al 2010;Kerschbaum et al 2011). An organisation loses private information related to its supply chain can negatively impact future contractual decisions of its partners.…”
Section: Introductionmentioning
confidence: 99%